Construindo as bases de um império: um contraste entre as vidas de Marco Antônio e Augusto - José, Natália Frazão [UNESP] (Universidade Estadual Paulista Julio de Mesquita Filho, 2020)
The political-military disputes between the heir of Julius Caesar, future Augustus, and the General Marc Antony left indelible marks in the History of the formation of the Roman Empire. Your oppositions, as well your manifestations before the Roman Society, helped in the formation of perspectives about the period, in the creation of memories and forgetfulness that, over the centuries, were transmitted, assimilated and reassimilated, until they reach our present day. In this way, they created diverse and also opposing images about these personas, their lives and their deaths. Therefore, the purpose of this article is to briefly highlight some interpretations made about the lives and deaths of Marc Antony and Augustus in some ancient authors, trying to demonstrate that the dispute between them happens, equally, in the way in which one lives and dies.

As disputas político-militares entre o herdeiro de Júlio César, futuro Augusto, e o general Marco Antônio deixaram marcas indeléveis na História da formação do Império Romano. Seus entraves, assim como suas manifestações perante a sociedade romana, auxiliaram na formação das perspectivas sobre o período, na criação de memórias e esquecimentos que, ao perpassar dos séculos, foram transmitidas, assimiladas e reassimiladas, até chegarem aos nossos dias. Criaram, desta maneira, imagens diversas e, também, opostas, sobre estes personagens, suas vidas e suas mortes. Assim sendo, a proposta deste artigo é destacar brevemente algumas interpretações realizadas sobre as vidas e as mortes de Marco Antônio e Augusto em alguns autores antigos, procurando demonstrar que a disputa entre ambos acontece, igualmente, na maneira em que vivem e em que morrem.
Building the Bases of an Empire: The Dichotomy between the Lives and Deaths of Marc Antony and Augustus.
Keywords: Lifes; Roman Empire; Marc Antony; Augustus; Vidas; Império Romano; Marco Antônio; Augusto